Major TCR Repertoire Perturbation by Immunodominant HLA-B*44:03-Restricted CMV-Specific T Cells - Attaf, Meriem; Malik, Amna; Severinsen, Mai C.; Roider, Julia; Ogongo, Paul; Buus, Søren; Ndung'u, Thumbi; Leslie, Alasdair; Kløverpris, Henrik N.; Matthews, Philippa C.; Sewell, Andrew K.; Goulder, Philip (Frontiers in Immunology, 2018)
Lack of disease during chronic human cytomegalovirus (CMV) infection depends on the maintenance of a high-frequency CMV-specific T cell response. The composition of the T cell receptor (TCR) repertoire underlying this response remains poorly characterised, especially within African populations in which CMV is endemic from infancy. Here we focus on the immunodominant CD8+ T cell response to the immediate-early 2 (IE-2)-derived epitope NEGVKAAW (NW8) restricted by HLA-B*44:03, a highly prevalent response in African populations, which in some subjects represents >10% of the circulating CD8+ T cells. Using pMHC multimer staining and sorting of NW8-specific T cells, the TCR repertoire raised against NW8 was characterised here using high-throughput sequencing in 20 HLA-B*44:03 subjects. We found that the CD8+ T cell repertoire raised in response to NW8 was highly skewed and featured preferential use of a restricted set of V and J gene segments. Furthermore, as often seen in immunity against ancient viruses like CMV and Epstein-Barr virus (EBV), the response was strongly dominated by identical TCR sequences shared by multiple individuals, or ‘public’ TCRs. Finally, we describe a pair ‘superdominant’ TCR clonotypes, which were germline or nearly germline-encoded and produced at remarkably high frequencies in certain individuals, with a single CMV-specific clonotype representing up to 17% of all CD8+ T cells. Given the magnitude of the NW8 response, we propose that this major skewing of CMV specific immunity leads to massive perturbations in the overall TCR repertoire in HLA-B*44:03 individuals.